Dynamic genetic architecture of metabolic syndrome attributes in the rat - Šeda, Ondřej; Liška, František; Křenová, Drahomíra; Kazdová, Ludmila; Šedová, Lucie; Zima, Tomáš; Peng, Junzheng; Pelinková, Květa; Tremblay, Jojanne; Hamet, Pavel; Křen, Vladimír (Physiological genomics, 2005)
The polydactylous rat strain (PD/Cub) is a highly inbred (F > 90) genetic model of metabolic syndrome. The aim of this study was to analyze the genetic architecture of the metabolic derangements found in the PD/Cub strain and to assess its dynamics in time and in response to diet and medication. We derived a PD/Cub x BN/Cub (Brown Norway) F2 intercross population of 149 male rats and performed metabolic profiling and genotyping and multiple levels of genetic linkage and statistical analyses at five different stages of ontogenesis and after high-sucrose diet feeding and dexamethasone administration challenges. The interval mapping analysis of 83 metabolic and morphometric traits revealed over 50 regions genomewide with significant or suggestive linkage to one or more of the traits in the segregating PD/Cub x BN/Cub population. The multiple interval mapping showed that, in addition to "single" quantitative train loci, there are more than 30 pairs of loci across the whole genome significantly influencing the variation of particular traits in an epistatic fashion. This study represents the first whole genome analysis of metabolic syndrome in the PD/Cub model and reveals several new loci previously not connected to the genetics of insulin resistance and dyslipidemia. In addition, it attempts to present the concept of "dynamic genetic architecture" of metabolic syndrome attributes, evidenced by shifts in the genetic determination of syndrome features during ontogenesis and during adaptation to the dietary and pharmacological influences.
Keywords: Insulin Resistance; Rats, Inbred BN; dexamethason; Dyslipidemias; fenotyp; Male; Phenotype; Rats, Inbred Strains; inzulinová rezistence; potkani inbrední BN; Dexamethasone; mužské pohlaví; metabolický syndrom; Genetic Linkage; Metabolic Syndrome; krysa rodu Rattus; lokus kvantitativního znaku; Animals; dyslipidemie; genetická vazba; Quantitative Trait Loci; zvířata; Rats; antiflogistika; Anti-Inflammatory Agents; zvířata kongenní; Sucrose; Animals, Congenic